Culture, User Behaviour and Interaction in Online Social Networks (OSNs) - Kyriakoullis, Leantros (My University, 2022)
The notion of culture has been of great interest by the researchers in recent years, without excluding the HCI community. The HCI community examined how users behave depending on their cultural background and proposed ways for developing more acceptable user interfaces reflecting the user’s cultural background. A number of design guidelines having culture in mind have been proposed, aiming to improve the overall user experience of the corresponding target group. Several studies examining culture have also associated user behavior with Hofstede’s cultural dimensions. Despite the cultural differences, the recent success of Online Social Networks (OSNs) illustrated that a single platform can be designed and used by a broader audience. Given the high participation levels across the globe, users overcame any concerns related to the platform (functional/design) and are eager to use it regardless of their diverse cultural background. Here we discuss the major forces that are driving Facebook use. We first employed phenomenography, to explore cultural values of Greek Cypriot users in Facebook and then conducted a survey study targeting five different cultural groups. For cross-culture analysis, we utilized principal components analysis (PCA) and analysed the derived components using various statistical methods, including parametric and non-parametric tests. Results reveal that information-seeking followed by forming connections with others (social connectedness) are major motivators for Facebook use. At the same time, differences between the cultural groups have been observed, for instance, Facebook intensity, privacy concerns and trust.
Keywords: Social Networks